Hubungan antara Tingkat Stres dan Risiko Terjadinya Gastroesophageal Reflux Disease pada Mahasiswa Kedokteran - Kambey, Dylan G. H.; Ong, Hardianto S. (Medical Scope Journal, 2026)
Abstract: Gastroesophageal reflux disease (GERD) is a chronic digestive disorder that can be exacerbated by various factors, one of which is stress. Medical students are considered a group highly susceptible to stress due to demanding academic pressures, which potentially increase their risk of developing GERD. This study aimed to analyze the relationship between the level of stress and the risk of GERD among students of the Medical Study Program at Universitas Tarumanagara. The study employed an analytical quantitative design with a cross-sectional approach. A total of 135 respondents were selected using cluster random sampling. Data were collected using the Perceived Stress Scale (PSS-10) and the GERD Questionnaire (GERD-Q). Bivariate analysis was conducted using the chi-square test with a significance level of p<0.05. The results showed that 80% of respondents experienced mild to moderate stress, and 20% experienced severe stress. Additionally, 19.3% of respondents were at risk of GERD. Statistical analysis revealed a significant relationship between stress and GERD risk (p=0.019), with a prevalence risk ratio (PRR) of 2.5, indicating that students experiencing severe stress were 2.5 times more likely to develop GERD compared to those with mild to moderate stress. In conclusion, high stress levels significantly contribute to an increased risk of GERD among medical students. Therefore, interventions such as stress management and healthy lifestyle education should be implemented to reduce the incidence of GERD in this population. Keywords: stress; GERD; medical students; PSS-10; GERD-Q    Abstrak: Gastroesophageal reflux disease (GERD) merupakan gangguan pencernaan kronis yang dapat diperburuk oleh berbagai faktor, salah satunya stres. Mahasiswa kedokteran tergolong kelompok yang rawan mengalami stres tinggi akibat tuntutan akademik yang berat, yang berpotensi meningkatkan risiko GERD. Penelitian ini bertujuan untuk menganalisis hubungan tingkat stres dengan risiko terjadinya GERD pada mahasiswa Program Studi Kedokteran Universitas Tarumanagara. Jenis penelitian ialah kuantitatif analitik dengan desain potong lintang. Sampel berjumlah 135 responden yang dipilih menggunakan metode cluster random sampling. Data dikumpulkan melalui kuesioner Perceived Stress Scale (PSS-10) dan GERD Questionnaire (GERD-Q). Analisis bivariat menggunakan uji chi-square dengan tingkat signifikansi p<0,05. Hasil penelitian mendapatkan sebanyak 80% responden mengalami stres ringan-sedang dan 20% responden mengalami stres berat. Sebanyak 19,3% responden memiliki risiko mengalami GERD. Hasil uji statistik menunjukkan hubungan bermakna antara stres dan risiko GERD (p=0,019), dengan rasio prevalensi risiko (PRR) sebesar 2,5, yang menunjukkan bahwa mahasiswa dengan stres berat memiliki risiko 2,5 lebih besar mengalami GERD dibandingkan dengan yang mengalami stres ringan-sedang. Simpulan penelitian ini ialah tingkat stres berpengaruh bermakna terhadap peningkatan risiko GERD pada mahasiswa kedokteran. Oleh karena itu, intervensi berupa manajemen stres dan edukasi gaya hidup sehat perlu diterapkan guna menurunkan risiko kejadian GERD di kalangan mahasiswa Kata kunci: stres; GERD; mahasiswa kedokteran; PSS-10; GERD-Q